2010
DOI: 10.1089/scd.2010.0201
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Stem Cells and Their Origins: Significance in Developmental Biology

Abstract: Adult corneal stem cells (SCs) have been the subject of substantial research over the past 2 decades, with promising clinical applications being devised, refined, and tried. However, there have been few studies on the early development of these cells in humans, perhaps due to ethical and practical constraints. This review highlights work that has yielded significant insights from developmental studies in the cornea and other SC repositories. This field merits further research to improve our current knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 114 publications
0
15
0
Order By: Relevance
“…In the mammalian cornea, epithelial cells with strong proliferative capacity and stem cell-like properties are initially distributed across the entire cornea (Chung et al, 1992;Collinson et al, 2002;Davies et al, 2009). As the embryo develops, corneal stem cells become restricted to the peripheral edge of the cornea, the limbus (Davies and Di Girolamo, 2010). This shift in corneal stem cell location is reflected in the clonal composition of the cornea during the course of development.…”
Section: Long-term Clonal Analyses In the Corneamentioning
confidence: 99%
See 1 more Smart Citation
“…In the mammalian cornea, epithelial cells with strong proliferative capacity and stem cell-like properties are initially distributed across the entire cornea (Chung et al, 1992;Collinson et al, 2002;Davies et al, 2009). As the embryo develops, corneal stem cells become restricted to the peripheral edge of the cornea, the limbus (Davies and Di Girolamo, 2010). This shift in corneal stem cell location is reflected in the clonal composition of the cornea during the course of development.…”
Section: Long-term Clonal Analyses In the Corneamentioning
confidence: 99%
“…In the cornea, it has long been believed that epithelial stem cells are located exclusively in the limbus and that corneal clones are formed by centripetal growth from the limbus (Davies and Di Girolamo, 2010;Lavker et al, 2004). Interestingly, new evidence suggest that corneal stem cells might be scattered over the entire cornea and that corneal clones may be formed by centrifugal, rather than centripetal, growth (Majo et al, 2008).…”
Section: Clonal Analysesmentioning
confidence: 99%
“…This is somewhat peculiar in evolutionary sense especially when the directly adjacent conjunctiva is maintained in the same way as any other epithelia [134] . In fetal eyes, adult LSC markers are found in the basal layer across the cornea [135,136] and it is unknown how the markers become segregated in the limbus during development. Investigation of limbal organogenesis has raised a possibility that the limbal papillary structures are mere developmental remnants.…”
Section: Developmental Origin Of Limbusmentioning
confidence: 99%
“…Investigation of limbal organogenesis has raised a possibility that the limbal papillary structures are mere developmental remnants. The limbus does not develop until eyelids open and the ocular surface is exposed to amniotic fluid [135,136] . The papillary structures of the limbus do not form until post-natal life [137] .…”
Section: Developmental Origin Of Limbusmentioning
confidence: 99%
“…Several recent studies showed that under appropriate culture conditions, ESCs can differentiate into corneal epithelial cell (CEC)-like cells, [24][25][26][27] which strongly expressed specific terminally differentiated CEC markers CK3, CK12, and Cx43/50. However, the proliferative capacity of these CEC-like cells was limited and could hardly subculture in vitro.…”
Section: Introductionmentioning
confidence: 99%